O movimento sindical na UFES : um estudo sob a ótica dos servidores técnico administrativos - Baptista, Alcimere Cristiani Degen (2015)
Given that unions are the fundamental building blocks to worker protection it was intended , through this study , find what the opinion of the technical administrative server and the trade union movement held in the Federal University of Espírito Santo ( UFES ) . Before that, however , sought to meet the general and specific objectives that guide the subject by means of the theoretical framework and field research surveys . This study is justified by the importance of the entity in the life of technical administrative server of the university, specifically pertaining to the representation of the organization from the perspective of the server, in addition, the analysis also offers the opportunity to conduct further research to contribute to the improvement the communicability between institution x server x entity. In the theoretical framework were approached the study of the history of trade unionism in Brazil and UFES , the impact of the neoliberal system with the unions, the construction of labor and trade union structures in the public service and the means of dissemination and marketing employees for union communication in Brazil . The fieldwork took place in two stages , two methodological techniques were used : a quantitative analysis was developed from the survey carried out with the administrative staff of the University servers and qualitative analysis , carried up interviews with the coordination responsible for communication the union and the university director . At the end it was found that there is evidence that the communication significantly affects the representativeness of the entity for both the server and the institution . This noted, the proposal is that the entity rethink programs and actions that result in a greater interest in the work to make it reflect on your life at work, for more efficient means of communication.